Urban Religion in Late Antiquity - Urciuoli, Emiliano Rubens (Religionsgeschichtliche Versuche und Vorarbeiten, 2021)
Aim of the volume is the analysis of the entanglement of religious communication and city life during an arc of time that is characterised by dramatic and even contradicting developments. Bringing together textual analyses and archaelogical case studies in a comparative perspective, the volume zooms in on the historical context of the advanced imperial and late antique Mediterranean space (2nd-8th centuries CE).